Two-Eyed Seeing: Mathematics and Indigenous Traditions and Cultures - Jungic, Veselin (Western Libraries, University of Western Ontario, 2022)
Elder Albert Marshal of the Mi’kmaw Nation describes “two-eyed seeing” as the ability to see with the strength of Indigenous knowledge from one eye while seeing with the strength of Western knowledge from the other. This dual perspective can be applied to many aspects of life, including mathematics. In this article, through a series of examples, I will explore the concept of “two-eyed seeing” related to traditional knowledge and mathematical knowledge.